Pengaruh Psikoedukasi terhadap Tingkat Kecemasan pada Pasien Pre Operasi Fraktur Usia Remaja di RSUD Dr. Pirngadi Medan - Nurul Haflah; Youlanda Sari; Vitri Rokhima (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
This study aims to determine the effect of psychoeducation on the anxiety of adolescent preoperative fracture patients. Fracture is an injury to the musculoskeletal system that can occur as a result of an accident. One of the treatment of fracture is by surgery. which causes anxiety. Psychoeducational therapy is an intervention that can be done to reduce anxiety. Research Design One group pre test post test. The research sample with total sampling technique was 30 respondents. Data analysis using Paired t-test. The results showed that there was a difference in the average level of anxiety of respondents before and after psychoeducation with a difference of 4.6 (p value 0.000) and there was an effect of psychoeducation on the decrease, indicating that there was an effect of psychoeducation on reducing the anxiety level of preoperative fracture patients.